Emerging Approaches of Cell‐Based Nanosystems to Target Cancer Metastasis. (8th September 2019) - Gong, Xiang; Li, Jie; Tan, Tao; Wang, Zhiwan; Wang, Hong; Wang, Yuqi; Xu, Xiaoxuan; Zhang, Zhiwen; Li, Yaping
Abstract: Cancer metastasis accounts for the high mortality of cancer‐related deaths and the therapy is greatly challenged by the limited drug delivery efficiency. Inspired by the essential role of culprit cancer cells and versatile accessory cells during cancer metastasis, diverse cell‐based nanosystems (CBNs) are emerging as attractive and encouraging drug delivery platforms to target cancer metastasis. Herein, the authors focus on the emerging strategies of versatile CBNs that synergistically combine the merit of source cells and nanoparticles for antimetastasis therapy. CBNs are usually comprised of natural nanosized vesicles, cell membrane camouflaged nanoparticles, and bioengineered living cell vehicles. The authors discuss the rationality and advances of various CBNs in targeting different stages of cancer metastasis, including primary tumor, circulating tumor cells (CTCs), and distant metastasis as well as the tumor immune microenvironments (TIM). On this basis, this review provides some feasible perspectives on designing CBNs to enhance the drug delivery efficiency for treating cancer metastasis. Abstract : Metastasis is the predominant cause of cancer‐related deaths, but the therapy is greatly challenged by the limited drug delivery efficiency. Inspired by the biological properties of diverse cells during cancer metastasis, the authors discuss the emerging approaches of versatile cell‐based nanosystems as attractive and feasible drug delivery platform to target different stages of cancer metastasis.